2004
DOI: 10.21273/jashs.129.3.0433
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Potassium Permanganate Impregnated into Alumina Beads to Reduce Atmospheric Ethylene

Abstract: A systematic study was conducted on the ability of potassium permanganate absorbent to remove low levels of ethylene from the atmosphere. Absorption of potassium permanganate onto alumina beads by dipping in a saturated solution was maximal at 2 g/100 g after 2 hours at 20 °C and 4 g/100 g after 1 hour at 65 °C. Commercial alumina-based absorbents were found to contain potassium permanganate at 2.7 to 6.0 g/100 g suggesting many are prepared at elevated temperature. Trials in a closed system at 20 °C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 13 publications
1
39
0
4
Order By: Relevance
“…Agents that can remove ethylene have long been identified and some of them have been succeeded in commercial application, such as potassium permanganate (Will and Warton, 2004;Bhutia et al, 2011), activated carbon (Bailén et al, 2006) and zeolite (Aday and Caner, 2011;Esturk et al, 2014). Activated carbon and zeolite are often used as supporters for preparing ethylene absorbers, since they are relatively inexpensive, possess a complex porous structure and high surface area to support catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Agents that can remove ethylene have long been identified and some of them have been succeeded in commercial application, such as potassium permanganate (Will and Warton, 2004;Bhutia et al, 2011), activated carbon (Bailén et al, 2006) and zeolite (Aday and Caner, 2011;Esturk et al, 2014). Activated carbon and zeolite are often used as supporters for preparing ethylene absorbers, since they are relatively inexpensive, possess a complex porous structure and high surface area to support catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The ethylene binding inhibitor is believed to bind irreversibly to ethylene receptors at very low concentrations (nl l À1 ), blocking or delaying the maturation processes normally induced by ethylene. When used appropriately, ethylene scavenging technologies, such as high temperature catalytic degradation (Martínez-Romero et al, 2009), activated carbon (Bailén et al, 2006) and potassium permanganate (KMnO 4 )-promoted materials (Will & Warton, 2004) can reduce ethylene levels in stored environments and therefore help maintain postharvest quality of climacteric fruits. Recently, a newly developed palladium (Pd)-promoted material (now registered as e + Ò Ethylene Remover) was shown to be effective at removing ethylene at low temperatures to sub-physiologically active levels and, accordingly, to effectively delay the climacteric-induced ripening of avocado cv.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium permanganate is commercially available impregnated into various inert substrates from a diverse range of manufacturers in many countries, but the barrier to better commercial uptake would seem to be the lack of definitive studies determining the actual amount of potassium permanganate required to keep ethylene at a sufficiently low concentration to maintain quality in individual produce for the desired market period under specific storage conditions. Wills and Warton highlighted some of the issues when they showed that temperature, humidity and amount of absorbent all have an impact on the efficiency of ethylene removal. They also found that the efficiency of ethylene removal had declined to 10% of incoming ethylene when close to 50% of the original potassium permanganate was still present in the alumina beads.…”
Section: Methods For Reducing Ethylenementioning
confidence: 99%